PENGARUH KUALITAS PRODUK DAN PEMASARAN DIGITAL TERHADAP LOYALITAS KONSUMEN YANG DIMEDIASI KEUNGGULAN BERSAING PADA JASA FOTO CITA-CITAKU DI SINGARAJA - Sudarnaya, Ketut; Mahe, Agipta (Jurnal Daya Saing, 2025)
This study aims to determine the effect of product quality and digital marketing on consumer loyalty mediated by competitive advantage at Jasa Foto Cita-Citaku Di Singaraja. The data analysis technique used in this study is the Structural Equation Modeling (SEM) based on SEM variance, which is known as Partial Least Square (PLS) visual version 3.0. The results of this study indicate that the path coefficients can be seen that product quality has a positive and significant effect on consumer loyalty at Jasa Foto Cita-Citaku in Singaraja. Digital marketing has a positive and significant effect on consumer loyalty at Jasa Foto Cita-Citaku in Singaraja. Product quality has a positive and significant effect on competitive advantage at Jasa Foto Cita-Citaku in Singaraja. Digital marketing has a positive and significant effect on consumer competitive advantage at Jasa Foto Cita-Citaku in Singaraja. Competitive advantage has a positive and significant effect on consumer loyalty at Jasa Foto Cita-Citaku in Singaraja. Product quality has a positive and significant effect on consumer loyalty mediated by competitive advantage at Jasa Foto Cita-Citaku in Singaraja. Digital marketing has a positive and significant influence on consumer loyalty mediated by competitive advantage at My Dream Photo Services in Singaraja.